Prayer or spiritual healing as adjuncts to conventional care: a cross sectional analysis of prevalence and characteristics of use among women. Issue 6 (25th June 2015) - Rao, Angela; Sibbritt, David; Phillips, Jane L; Hickman, Louise D
Abstract : Objectives: To determine the prevalence and characteristics of users of prayer or spiritual healing among women. Design and setting: This cross sectional study was conducted as a part of the Australian Longitudinal Study on Women's Health (ALSWH), a 20-year study that examines various factors affecting women's health and well-being. Participants: The sample used in the current study were women from the 1946–1951 cohort (n=9965) (59–64 years) who were surveyed in 2010. Outcome measures: Use of prayer or spiritual healing; demographic factors and measures of health status. χ 2 Tests, analyses of variance (to determine associations) and a stepwise backward logistic regression model (for the most significant predictors) using a likelihood ratio test were used to determine the outcome measures. Results: It is estimated that 26% of Australian women from the 1946–1951 cohort (aged 59–64 years) use prayer or spiritual healing on a regular basis. Women were significantly more likely to use prayer or spiritual healing if they were non-smokers, non-drinkers or low-risk drinkers, had symptoms of severe tiredness (OR 1.25; 95% CI 1.12 to 1.40), depression, (OR 1.30; 95% CI 1.11 to 1.53), anxiety (OR 1.33; 95% CI 1.15 to 1.53), diagnosed cancer (OR 1.84; 95% CI 1.28 to 2.65) or other major illnesses (OR 1.43; 95% CI 1.18 to 1.75) and used other complementary therapies. Conclusions: A significant proportion of adult women are using prayer or spiritual healing. Given that prayer or spiritual healing was significantly associated with health symptoms, chronic illnesses and positive health seeking behaviours, respect for prayer or spiritual healing practices is required within health care settings. Future research is recommended around specific populations using prayer or spiritual healing, reasons for their use and potential benefits on health related outcomes and general well-being.